2006
DOI: 10.1042/ba20050169
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active vascular endothelial growth factor as a bacterial recombinant glutathione S‐transferase fusion protein

Abstract: Human VEGF121 (vascular endothelial growth factor isoform 121) was produced as a recombinant fusion protein with GST (glutathione S-transferase) in Escherichia coli. After affinity purification with glutathione, the GST-VEGF121 fusion protein preparation was used to obtain antibodies in mice against commercial hrVEGF (human recombinant VEGF) through immunization. It was also employed successfully to select specific antihuman VEGF antibody fragments of human origin employing phage-display technology. The fusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Some studies do not present any yield [ 49 , 54 ] or the data are unclear [ 38 ]. In other works, the yield of purified active VEGF 121 or VEGF 165 is between 1 mg and 5 mg per L of bacterial culture [ 50 , 52 , 53 ], which is similar to the yield of mutant VEGF 121 purified in this work. The yield of recombinantly expressed α 2 -PI 1-8 -VEGF 121 by Zisch et al was 11 mg/L [ 30 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Some studies do not present any yield [ 49 , 54 ] or the data are unclear [ 38 ]. In other works, the yield of purified active VEGF 121 or VEGF 165 is between 1 mg and 5 mg per L of bacterial culture [ 50 , 52 , 53 ], which is similar to the yield of mutant VEGF 121 purified in this work. The yield of recombinantly expressed α 2 -PI 1-8 -VEGF 121 by Zisch et al was 11 mg/L [ 30 ].…”
Section: Discussionsupporting
confidence: 83%
“…Studies comparing the biological activities of various VEGF preparations have not found any significant differences [ 53 , 63 ]. The biological activity was also comparable to that of the commercial standard in the case of VEGF proteins joined to uncleaved fusion partners, such as thioredoxin or GST [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 72%
“…GST-fused human VEGF isoform 121 (GST-hVEGF) was produced in E. coli as previously described [14]. Human VEGF isoform 121 (rhVEGF) was produced in CHO cells [15].…”
Section: Methodsmentioning
confidence: 99%
“…rVEGF was produced as a recombinant protein, with VEGF 165 fused to the carboxy-terminus of glutathione-S-transferase (GST)33. It has been previously shown that the presence of GST in the fusion protein does not affect the biofunctionality of VEGF33. Actually, the presence of a GST tag facilitates the purification steps and works as a “spacer” for linking the VEGF to the MNP.…”
Section: Resultsmentioning
confidence: 99%
“…We used GST alone produced from bacteria transformed with the empty pGEX6p-1 plasmid as control. For protein purification we followed the protocol published by Morera and colleagues33 with minor modifications. In particular, we transformed BL21 strain of E. coli with pGEX6P-VEGF and a single colony was inoculated in 10 ml LB medium.…”
Section: Methodsmentioning
confidence: 99%